Empires of vice : the rise of opium prohibition across Southeast Asia - Kim, Diana S., 1982- (Histories of economic life., 2020)
"Though today opiates are highly controlled substances and generally viewed as menaces to society, the opium trade was once licit and profitable, both for merchants and for the governments to which they paid taxes. During the late nineteenth century, British and French colonies in Southeast Asia drew up to fifty percent of their revenue from taxes on opium consumption. Given its profitability and European rulers' strenuous defence of opium as an integral part of managing an empire, how did both attitudes toward and laws about opium shift so dramatically by the mid-twentieth century? This book argues against the conventional understanding that opium prohibition was enacted as part of a wave of liberal humanitarianism or because doctors awoke to its dangers to users' wellbeing, and instead offers a more complex story. In examining the opium's fall from grace throughout British and French colonies in Southeast Asia from the 1860s to the 1940s, Diana Kim combines extensive archival research with her training in political science. This book reveals the key role minor colonial administrators played in the abolition process. Local administrators were players in intellectual debates and decision-making processes concerning opium, and the knowledge they produced-their records and observations-influenced the empire's revenue policies. The author's analysis of these processes challenges notions that states implement policies based on maximizing their revenue. By observing how opium prohibition was implemented differently and at different times across the region, Kim argues against the idea that the push for prohibition came from the metropole. Further, she reflects on the lasting legacies of prohibition and the implications for present-day politics and public regulation of vice crimes and illicit markets, making a statement about how vice is defined and how its regulation affects processes of state formation, colonial and otherwise"--